Mutation in Drosophila concentrative nucleoside transporter 1 alters spermatid maturation and mating behavior - Maaroufi, Houda Ouns; Pauchova, Lucie; Lin, Yu-Hsien; Wu, Bulah Chia-Hsiang; Rouhova, Lenka; Kucerova, Lucie; Vieira, Ligia Cota; Renner, Marek; Sehadova, Hana; Hradilova, Miluse; Zurovec, Michal (Frontiers in Cell and Developmental Biology, 2022)
Concentrative nucleoside transporters (Cnts) are unidirectional carriers that mediate the energy-costly influx of nucleosides driven by the transmembrane sodium gradient. Cnts are transmembrane proteins that share a common structural organization and are found in all phyla. Although there have been studies on Cnts from a biochemical perspective, no deep research has examined their role at the organismal level. Here, we investigated the role of the Drosophila melanogaster cnt1 gene, which is specifically expressed in the testes. We used the CRISPR/Cas9 system to generate a mutation in the cnt1 gene. The cnt1 mutants exhibited defects in the duration of copulation and spermatid maturation, which significantly impaired male fertility. The most striking effect of the cnt1 mutation in spermatid maturation was an abnormal structure of the sperm tail, in which the formation of major and minor mitochondrial derivatives was disrupted. Our results demonstrate the importance of cnt1 in male fertility and suggest that the observed defects in mating behavior and spermatogenesis are due to alterations in nucleoside transport and associated metabolic pathways.